Pengaruh CAR, ROA, FDR, dan BOPO terhadap Non Performing Financing pada Bank Muamalat Indonesia - Dea Apriyani; Ine Mayasari; Mochamad Edman Syarief (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Muamalat Bank have decline in financial performance. Muamalat Bank lacks capital because it provides too much corporate financing which has an impact on increasing non-performing financing. Besides that, the net profit of Muamalat Bank in 2019 decreasec significantly, namely by 92% and its operating costs rached Rp490 billion. This research was conducted to know the effect of the variable Capital Adequacy Ratio (CAR), Return On Assets (ROA), Financing to Deposit Ratio (FDR), and Operating Expenses per Operating Income (BOPO) on Non-Performing Financing (NPF) at Bank Muamalat. Indonesia. The sample used is the quarterly report published on the official website of Bank Muamalat. The research method used is quantitative research with multiple linear regression analysis and is supported by the Eviews software version 10 as a data processing application. The results of this study indicate that CAR and ROA have a negative and significant effect on the NPF of Bank Muamalat. Meanwhile, FDR and BOPO have a positive and significant effect on NPF.